Akulturasi Nilai-Nilai Budaya Lokal dan Keagamaan dan Pengaruhnya terhadap Perilaku-Perilaku Sosial - Jurna Roszi; Mutia Mutia (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2018)
This paper discusses the acculturation of Islam and traditions in the archipelago. The acculturation between Islam and local culture reinforces the concept of the harmony of Islam and local culture that can live hand in hand with their respective values, namely religious values and traditional values that have been acculturated and in direct contact. Acculturation is a concept to describe the long process of meeting two or more values between Islam and local values in which individuals, groups and communities live with the culture they already have. Historical and anthropological approaches are the approaches used in this study. Both of these approaches are used to observe and trace the processes that occur and the formation of a history that surrounds the community. From the search of history carried out it was found that Islam was inseparable from the influence of animist beliefs, dynamism, Hindu-Buddhist religion before Islam came. So that, when Islam comes and meets a pre-existing culture, it influences one another.